ITAREPS: information technology aided relapse prevention programme in schizophrenia - Spaniel, Filip; Vohlídka, Pavel; Hrdlicka, Jan; Kozený, Jirí; Novák, Tomás; Motlová, Lucie; Cermák, Jan; Bednarík, Josef; Novák, Daniel; Höschl, Cyril (Schizophrenia research, 2008)
ITAREPS presents a mobile phone-based telemedicine solution for weekly remote patient monitoring and disease management in schizophrenia and psychotic disorders in general. The programme provides health professionals with home telemonitoring via a PC-to-phone SMS platform that identifies prodromal symptoms of relapse, to enable early intervention and prevent unnecessary hospitalizations. Its web-based interface offers the authorized physician a longitudinal analysis of the dynamics and development of possible prodromes. This work presents preliminary findings from a one-year mirror-design follow-up evaluation of the programme's clinical effectiveness in 45 patients with psychotic illness. There was a statistically significant 60% decrease in the number of hospitalizations during the mean 283.3+/-111.9 days of participation in the ITAREPS, compared to the same time period before the ITAREPS entry (sign test, p<0.004). Variables significantly influencing the number of hospitalizations after the ITAREPS entry (medication compliance along with factors intrinsic to the ITAREPS, i.e. adherence to the programme and involvement of a family member) suggest a critical role of the programme in controlling the number of relapses and subsequent hospitalizations in psychosis.
Keywords: Treatment Outcome; Schizophrenia; Telemedicine; telemedicína; lidé; Remote Consultation; výsledek terapie; Patient Readmission; adherence pacienta; průzkumy a dotazníky; mužské pohlaví; Program Evaluation; hodnocení programu; Adult; Antipsychotic Agents; Secondary Prevention; Caregivers; hodnocení výsledků zdravotní péče; konzultace na dálku; Telephone; ženské pohlaví; Humans; Outcome Assessment, Health Care; osoby pečující o pacienty; Surveys and Questionnaires; pilotní projekty; Patient Compliance; Program Development; Schizophrenic Psychology; schizofrenie; antipsychotika; telefon; Pilot Projects; schizofrenie (psychologie); Hospitalization; hospitalizace; dospělí; Female; rozvoj plánování; znovupřijetí pacienta; sekundární prevence; Male